Business, government and community relationships - McCabe, Margaret; Whiteley, Alma; Thomas, Gail (World Business Institute, 2007)
The paper reports on an exploratory study having its genesis in the Parliamentary Joint Committee on Corporations and Financial Services (2006). The triadic relationship between business, government and the community is explored within the Australian context. The authors explore the perceived reality (the way these relationships are seen to operate) and the ideal (the way they are seen to be designed to operate) with respect to corporate social responsibility and the barriers that prevent the ideal from being the reality. Using quotes from participant interviews, the authors conclude that while business and government are aligned to form a stable power base within the triad, community is perceived to be subject to judgements or decisions determined by the other two entities. A waxing and waning of community strength is identified and the nature of this fluid position and its attendant consequences for the exertion of power are suggested as issues for future research.